Dementia vs. somatic conditions in the German LTC-system: A longitudinal analysis - Daniel Ehing; Christian Hagist (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2015)
This paper analyzes prevalence and incidence rates as well as survival times for people above the age of 60 years with a dementia disorder and/or a long-term care status. Using claim data from a social sickness funds in Germany (AOK-Plus), we show that there exists a with age increasing gap between the prevalence of women and men for both fields of study. This discrepancy cannot be explained completely by our estimated incidence rates and is caused by different survival times in long-term care and dementia. In long-term care 50 percent of all women (men) are dead after 44 (25) months, whereas about 57 (49) percent of all women (men) with dementia are alive after the end of our 48 month long observation period. The lower mortality of people with dementia is mainly explained by a large share of people who are not eligible for the German long-term care system. Estimating several cox models shows that the hazard of dying in long-term care increases with age and care level. However younger people with a dementia disorder show lower mortality rates in long-term care than their respective peer group without dementia. Looking at the present value of all long-term care costs for people with and without a dementia diagnosis, we find total average costs of 68,600 (44,857) Euro for women (men) without dementia. Due to their extended stay in nursing home care, women (men) with dementia are more expensive (80,201 (49,793) Euro).
Keywords: I19; H55; 330; dementia; long-term care; incidence rate; prevalence rate; survival analysis; costs of long-term care